PENGARUH ATTITUDE TOWARD BEHAVIORAL, SUBJECTIVE NORM, PERCEIVED BEHAVIORAL CONTROL TERHADAP ENTREPRENEURIAL INTENTION - Widjaja, Marcellino; Dewi, Liliana (PERFORMA, 2023)
The purpose of this research is to test the factors that affect entrepreneurial intention on Universitas Ciputra and Petra Christian University students. Respondents in this research are 180 of 2017 IBM active students of Universitas Ciputra and Petra Christian University. Questionnaire collection is done through google form. In this research, it will use non probability sampling and data retrieval uses purposive sampling technique by using quantitative data type. The data that has been collected is processed by using multiple regression analysis technique. This research is based on three variables, that is, attitude towards behavioral, subjective norm, and perceived behavioral control. The results of this research state that subjective norm affect significant on entrepreneurial intention and attitude towards behaviour, perceived behaviour does not affect significant on entrepreneurial intention. Keywords : entrepreneurial intention, subjective norm, perceived behavioral control, attitude towards behaviour